We know the derivative of e^{x}, which is e^{x}.
(e^{x})' = e^{x}
We can find the derivative of e^{√sinx} using chain rule.
Find ᵈʸ⁄dₓ, if
y = e^{√sinx}
Let u = sinx.
y = e^{√u}
Let v = √u.
y = e^{v}
Now,
y = e^{v} ----> y is a function of v
v = √u ----> v is is a function of u
u = sinx ----> u is is a function of x
By chain rule, the derivative of y with respect to x :
Substitute y = e^{v}, v = √u and u = sinx.
Substitute v = √u.
Substitute u = sinx.
Therefore,
Kindly mail your feedback to v4formath@gmail.com
We always appreciate your feedback.
©All rights reserved. onlinemath4all.com
May 26, 23 12:27 PM
May 21, 23 07:40 PM
May 20, 23 10:53 PM